Continuous photon energy modulation in IMRT of pancreatic cancer - Zhang, Xile; Zhou, Fugen; Liu, Bo; Xiong, Tianyu; Bai, Xiangzhi; Wu, Qiuwen (Frontiers in Physics, 2023)
Purpose: To develop a novel IMRT optimization method based on the principle of photon energy synthesis that simultaneously optimizes fluence map and beamlet energy. The method was validated on pancreatic cancers to demonstrate the benefits of the additional degree of freedom of photon energy in IMRT.Previous work has demonstrated that the effect of a photon beam of known energy can be achieved by the combination of two existing energy photons in the proper ratio. It further implied that any energy photon can be synthesized. Based on this, we propose the concept of continuous beamlet energy modulation in IMRT, or IMRT-BEM. The IMRT-BEM was modeled as the simultaneous optimization of two fluence maps, one for the low energy beam and one for the high energy beam, and it was implemented in an in-house inverse planning system. The IMRT-BEM was applied on ten pancreatic cancer cases, where the IMRT-BEM plan was compared with single-energy IMRT plans of 6 MV (IMRT-6MV) and 15 MV photons (IMRT-15MV).The IMRT-BEM plan provides a noticeable reduction to the volume irradiated at the high dose level (PTV105%) for PTV, at least 24.7% (6.4 ± 6.8 vs 31.1 ± 18.7 (p=0.005) and 43.8 ± 19.8 (p=0.005) for IMRT-BEM, IMRT-6MV, and IMRT-15MV respectively). For target dose coverage, there were statistically significant improvements between the IMRT-BEM plans and the other two plans in terms of CI and HI. Compared to the IMRT-6MV plan, there were significant reductions in the Dmean of the spinal cord, liver, bowel, duodenum, and stomach. The irradiation volumes of the medium dose (V20Gy, and V40Gy) for the duodenum and bowel were reduced significantly. There were no significant differences between the IMRT-BEM and IMRT-15MV plans except for the Dmean of the spinal cord and the duodenum, the V20Gy, and V40Gy for the duodenum, and the V20Gy of the stomach.IMRT-BEM has certain dosimetric advantages for PTV and improves OAR sparing in pancreatic cancer, and can be effectively used in radiation treatment planning, providing another degree of freedom for planners to improve treatment plan quality.